Climate control on terrestrial biospheric carbon turnover - Eglinton, Timothy I.; Galy, Valier V.; Hemingway, Jordon D.; Feng, Xiaojuan; Bao, Hongyan; Blattmann, Thomas M.; Dickens, Angela F.; Gies, Hannah; Giosan, Liviu; Haghipour, Negar; Hou, Pengfei; Lupker, Maarten; et al. (Proceedings of the National Academy of Sciences, 2021)
Terrestrial vegetation and soils hold three times more carbon than the atmosphere. Much debate concerns how anthropogenic activity will perturb these surface reservoirs, potentially exacerbating ongoing changes to the climate system. Uncertainties specifically persist in extrapolating point-source observations to ecosystem-scale budgets and fluxes, which require consideration of vertical and lateral processes on multiple temporal and spatial scales. To explore controls on organic carbon (OC) turnover at the river basin scale, we present radiocarbon (C-14) ages on two groups of molecular tracers of plant-derived carbon-leaf-wax lipids and lignin phenols-from a globally distributed suite of rivers. We find significant negative relationships between the C-14 age of these biomarkers and mean annual temperature and precipitation. Moreover, riverine biospheric-carbon ages scale proportionally with basin-wide soil carbon turnover times and soil C-14 ages, implicating OC cycling within soils as a primary control on exported biomarker ages and revealing a broad distribution of soil OC reactivities. The ubiquitous occurrence of a long-lived soil OC pool suggests soil OC is globally vulnerable to perturbations by future temperature and precipitation increase. Scaling of riverine biospheric-carbon ages with soil OC turnover shows the former can constrain the sensitivity of carbon dynamics to environmental controls on broad spatial scales. Extracting this information from fluvially dominated sedimentary sequences may inform past variations in soil OC turnover in response to anthropogenic and/or climate perturbations. In turn, monitoring riverine OC composition may help detect future climate-change-induced perturbations of soil OC turnover and stocks.
Keywords: Carbon cycle; carbon turnover times; fluvial carbon; plant biomarkers; radiocarbon